A universal polysaccharide conjugated vaccine against O111 E. coli - Andrade, Gabrielle R (Hum Vaccin Immunother, 2014)
E. coli O111 strains are responsible for outbreaks of blood diarrhea and hemolytic uremic syndrome throughout the world. Because of their phenotypic variability, the development of a vaccine against these strains which targets an antigen that is common to all of them is quite a challenge. Previous results have indicated, however, that O111 LPS is such a candidate, but its toxicity makes LPS forbidden for human use. To overcome this problem, O111 polysaccharides were conjugated either to cytochrome C or to EtxB (a recombinant B subunit of LT) as carrier proteins. The O111-cytochrome C conjugate was incorporated in silica SBA-15 nanoparticles and administered subcutaneously in rabbits, while the O111-EtxB conjugate was incorporated in Vaxcine(TM), an oil-based delivery system, and administered orally in mice. The results showed that one year post-vaccination, the conjugate incorporated in silica SBA-15 generated antibodies in rabbits able to inhibit the adhesion of all categories of O111 E. coli to epithelial cells. Importantly, mice immunized orally with the O111-EtxB conjugate in Vaxcine(TM) generated systemic and mucosal humoral responses against all categories of O111 E. coli as well as antibodies able to inhibit the toxic effect of LT in vitro. In summary, the results obtained by using 2 different approaches indicate that a vaccine that targets the O111 antigen has the potential to prevent diarrhea induced by O111 E. coli strains regardless their mechanism of virulence. They also suggest that a conjugated vaccine that uses EtxB as a carrier protein has potential to combat diarrhea induced by ETEC.